Recent insights into the role of L1CAM in cancer initiation and progression. Issue 12 (17th July 2020) - Altevogt, Peter; Ben‐Ze'ev, Avri; Gavert, Nancy; Schumacher, Udo; Schäfer, Heiner; Sebens, Susanne
Abstract: First described as a neuronal cell adhesion molecule, L1CAM was later identified to be present at increased levels in primary tumors and metastases of various types of cancer. Here, we describe the multifaceted roles of L1CAM that are involved in diverse fundamental steps during tumor initiation and progression, as well as in chemoresistance. Recently, Ganesh et al reported that L1CAM identifies metastasis‐initiating cells in colorectal carcinoma exhibiting stem‐like cell features, increased tumorigenic potential and enhanced chemoresistance. In this review, we highlight recent advances in L1CAM research with particular emphasis on its role in de‐differentiation processes and cancer cell stemness supporting the view that L1CAM is a powerful prognostic factor and a suitable target for improved therapy of metastatic and drug‐resistant tumors.